Role of infectious agents in cancer pathogenesis and therapy - Ezichi F. Ofoezie; Chinwendu A. Ogbonna; Sandra C. Olisakwe; Chioma J. Anunobi; Ezinne T. George; Simeon Babarinde; Chidera G. Chukwuemeka; Uzochukwu E. Ogbonna; Chibuzo C. Amafili; Chibuzo V. Alisigwe; Onyinyechi J. Omaba; Henry N. Ogbonna (The Microbe)
Infectious agents contribute substantially to cancer pathogenesis, representing a significant proportion of the global cancer burden. This review delves into the complex mechanisms pathogens drive oncogenesis, emphasizing chronic inflammation, immune evasion, genetic integration, and epigenetic alterations. These processes enable infectious agents such as Epstein-Barr Virus (EBV), Hepatitis B and C viruses (HBV, HCV), Helicobacter pylori and Human Papillomavirus (HPV) to disrupt host cellular homeostasis and facilitate tumor development. Emerging therapeutic strategies are also explored, including pathogen-specific immunotherapies such as prophylactic and therapeutic vaccines, immune checkpoint inhibitors targeting infected cells, and cutting-edge gene-editing technologies like CRISPR. Additionally, the review highlights antiviral and antibacterial therapies aimed at oncogenic pathways, along with the integration of these modalities with conventional cancer treatments. These developments highlight the urgent need for creative, multidisciplinary methods to enhance the prognosis of cancers linked to pathogens.